Efeito de Reforçadores Condicionados Específicos em Classes Ordinais em Humanos - De Assis, Grauben José Alves (2015)
The explanation according to which equivalence classes are formed by contingencies of reinforcement, has the implication that responses and reinforcer stimuli would also be included among its members. Empirical support for this theory comes from experiments using specific reinforcers to each potential class, both in the context of conditional discrimination as in the simple discrimination context, in the latter case in combination with systematic reversals, in which S+ and S-functions of the discriminative stimuli are constantly reversed. In the two cases, appropriated tests showed the inclusion of reinforcer stimuli as members of the equivalence classes. These results encourage hypothesize that reinforcer stimuli also participate in ordinal classes, which are defined by the properties: asymmetry, inflexibility, transitivity, substitutability and connectedness. Preliminary, this study tested an experimental strategy as a first step toward an investigation on the inclusion of reinforcing stimuli as members of sequential classes. Its aim was to investigate the effect of specific conditioned reinforcers in the formation of ordinal classes. In the presence of one conditional stimulus, six university students had to make sequences of abstract pictures in a determined order that were followed by the presentation of one musical passage. In the presence of another conditional stimulus, the same stimuli had to be sequenced in the reverse order, producing another musical excerpt. Tests showed that in addition to the emergence of defining properties of ordinal classes, the musical excerpts exchanged their reinforcing function for the conditional stimulus function.